Power consumption analysis of digital filters with sparse coefficients - Tan, Fu Loong. (2013)
Digital finite impulse response filters (FIR) are commonly used in various applications of signal processing and communication. Classical FIR filter design emphasizes on developing numerical methods, which can achieve ideal solutions under some criterion. However, the implementation of FIR filters may require a large number of multipliers, especially when design specifications are extremely stringent. One of potential ways to efficiently realize FIR filters is to reduce the number of arithmetic operations, which can be taken into account during the stage of designing sparsity filters. In sparse filter designs, the multipliers corresponding to the zero-valued coefficients can be omitted, which consequently reduce the complexity of implementation. However, this would inevitable result in the filter order to be increased. In this project, the power consumptions of the sparse and non-sparse filters are investigated to demonstrate under what condition the sparse filter may achieved in power savings.